Oxidation of linezolid by permanganate in acidic medium: Pd(II) catalysis, kinetics and pathways - Kulkarni, Raviraj M.; Hanagadakar, Manjunath S.; Malladi, Ramesh S.; Santhakumari, B.; Nandibewoor, Sharanappa T. (Progress in Reaction Kinetics and Mechanism, 2016)
The uncatalysed and Pd(II)-catalysed oxidation of linezolid (LNZ) by permanganate (PMGT) in acidic medium was carried out in the pH range from 3.0 to 6.0. The second order rate constants were found to decrease with increase in pH. The apparent second order rate constants for the uncatalysed reaction were, for example, k `'(app)= 6.32 dm(3) mol(-1) at pH 3.0 and k `'(app). = 2.64 dm(3) mol(-1) s(-1) at pH 6.0 and at 25 +/- 0.2 degrees C and for the Pd(II)-catalysed reaction the total apparent second order rate constants were k `'(app) = 75.5 dm(3) mol(-1) s(-1) at pH 3.0 and k `'(app). = 45.66 dm(3) mol(-1) s(-1) at pH 6.0 and at 25 +/- 0.2 degrees C. The rate constant of the Pd(II)-catalysed reaction was thus ten times higher than for the uncatalysed reaction. The oxidation products of the reaction were identified using high resolution LC-MS. The reaction progresses via formation of a Pd-LNZ complex, which reacts with acidic PMGT to form an intermediate compound, which then decomposes to give oxidised products. The dependence of the rate of reaction on various parameters, such as pH, temperature, [LNZ], [PMGT], [Pd(II)], dielectric constant and ionic strength were studied and activation parameters for the reaction were evaluated and discussed.